The Role of Erythropoietin and Bone Marrow Concentrate in the Treatment of Osteochondral Defects in Mini-Pigs - Betsch, Marcel (Public Library of Science, 2014)
BACKGROUND: All available treatment options for osteochondral and chondral defects do not restore hyaline cartilage and are limited to decreasing associated pain, and maintaining or improving joint function. The purpose of this study was to evaluate the potential of erythropoietin (EPO) in combination with bone marrow aspiration concentrate (BMAC) in the treatment of osteochondral defects of mini-pigs. METHODS: 14 Goettinger mini-pigs, in which a 6×10 mm osteochondral defect in the medial femoral condyle of both knee joints was created, were randomized into four groups: biphasic scaffold alone, scaffold with EPO, scaffold with BMAC and scaffold in combination with EPO and BMAC. After 26 weeks all animals were euthanized and histological slides were evaluated using a modified ÓDriscoll Score. RESULTS: In the therapy groups, areas of chondrogenic tissue that contained collagen II were present. Adding EPO (p = 0.245) or BMAC (p = 0.099) alone to the scaffold led to a non-significant increase in the score compared to the control group. However, the combination of EPO and BMAC in the implanted scaffold showed a significant improvement (p = 0.02) in the histological score. CONCLUSION: The results of our study show that in mini-pigs, the combination of EPO and BMAC leads to an enhanced osteochondral healing. However, additional research is necessary to further improve the repair tissue and to define the role of MSCs and EPO in cartilage repair.